Current management of proton pump inhibitor-refractory gastroesophageal reflux disease - V. V. Tsukanov; A. V. Vasyutin; Yu. L. Tonkikh (Фундаментальная и клиническая медицина)
Here we review current concepts in diagnosis and treatment of proton pump inhibitor (PPI)-refractory gastroesophageal reflux disease (PPIGERD) which includes an insufficient response to daily PPI 8-week therapy in combination with pathological gastroesophageal reflux. Patients with PPI-GERD frequently suffer from non-acidic and asymptomatic gastroesophageal reflux. In developed countries, PPI-GERD accounts for 30-40% of all patients receiving PPIs. Diagnosis of PPIGERD is performed by means of clinical anamnesis, esophagogastroscopy and impedance-pH monitoring. PPI-GERD needs to be differentiated with functional heartburn, reflux hypersensitivity and nonerosive reflux disease. Functional heartburn is characterised by reference time with a esophageal pH < 4 and the absence of a link between reflux episodes and GERD symptoms. Reflux hypersensitivity is diagnosed with normal esophageal acid exposure and association of reflux episodes with symptoms of GERD. Nonerosive reflux disease can be diagnosed solely by evaluating pathological acid exposure (pH < 4 for > 6% of the time). Treatment of PPI-GERD includes diet and lifestyle modification to reduce weight in obese patients, optimization of PPI use, and administration of alginate, prokinetics, baclofen and other drugs. Surgical treatment is also widely used and provide good results.